About unrealization of tungsten lines up to the ground state in the nonideal plasma of pulse discharges in water - Fedorovich, O.A. (Вопросы атомной науки и техники, 2009)
The paper considers the dynamics of tungsten impurity absorption line appearance in the plasma channel of the pulse discharge in water (PDW) during the plasma relaxation process. In the initial stage of discharge (3 µs) any tungsten and hydrogen absorption line is not observed in the spectrum. The optical gap width ∆Е in the nonideal plasma exceeds 5.5 eV. After 20 µs in the process of plasma relaxation, the absorption lines appear in the spectrum. They correspond to transitions from the ground level to the levels with higher energies, not exceeding 3.24 eV, i.e. the gap width is 4.74 eV. After 53 µs the gap width decreases down to 2.22 eV. The estimations of the electron concentration in the plasma, obtained on the basis of the gap width, and on the plasma frequency, are in a good agreement.